1995
DOI: 10.1002/jcp.1041650224
|View full text |Cite
|
Sign up to set email alerts
|

Role of the α1β1 integrin complex in collagen gel contraction in vitro by fibroblasts

Abstract: Matrix remodeling, critical to embryonic morphogenesis and wound healing, is dependent on the expression of matrix components, their receptors, and matrix proteases. The collagen gel assay has provided an effective model for the examination of the functional role(s) of each of these groups of molecules in matrix remodeling. Previous investigations have indicated that collagen gel contraction involves the beta 1 integrin family of matrix receptors and is stimulated by several growth factors, including TGF-beta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 36 publications
7
105
0
Order By: Relevance
“…Fibroblasts interact with and attach to collagen matrices primarily through integrin ␣2␤1 but also with other integrins, including ␣1␤1, ␣11␤1, and ␣v␤3 (Klein et al, 1991;Schiro et al, 1991;Carver et al, 1995;Cooke et al, 2000;Tiger et al, 2001;Jokinen et al, 2004), and blocking antibodies against integrin ␣2␤1 slowed down the time course of fibroblast adhesion and spreading on collagen matrices consistent with previous findings.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Fibroblasts interact with and attach to collagen matrices primarily through integrin ␣2␤1 but also with other integrins, including ␣1␤1, ␣11␤1, and ␣v␤3 (Klein et al, 1991;Schiro et al, 1991;Carver et al, 1995;Cooke et al, 2000;Tiger et al, 2001;Jokinen et al, 2004), and blocking antibodies against integrin ␣2␤1 slowed down the time course of fibroblast adhesion and spreading on collagen matrices consistent with previous findings.…”
Section: Discussionsupporting
confidence: 85%
“…Surprisingly, this treatment did not cause cells to detach from collagen matrices although essentially 100% of the cells were removed from collagencoated coverslips. This difference in trypsin sensitivity suggested that the cells might be anchored to collagen matrices at least in part by an integrin-independent mechanism.Fibroblasts interact with and attach to collagen matrices primarily through integrin ␣2␤1 but also with other integrins, including ␣1␤1, ␣11␤1, and ␣v␤3 (Klein et al, 1991;Schiro et al, 1991;Carver et al, 1995;Cooke et al, 2000;Tiger et al, 2001;Jokinen et al, 2004), and blocking antibodies against integrin ␣2␤1 slowed down the time course of fibroblast adhesion and spreading on collagen matrices consistent with previous findings.Divalent cations also have been implicated in integrin activity (Gailit and Ruoslahti, 1988;Leitinger et al, 2000), and in the presence of 10 mM EDTA, cell adhesion to collagen matrices was almost completely inhibited. Yet, once the cells were attached, treatment with 10 mM EDTA was unable to release cells from collagen matrices, even though cells on collagen-coated coverslips detached completely.…”
supporting
confidence: 85%
See 3 more Smart Citations